2016
DOI: 10.1002/hipo.22672
|View full text |Cite
|
Sign up to set email alerts
|

Familiarity expands space and contracts time

Abstract: When humans draw maps, or make judgments about travel‐time, their responses are rarely accurate and are often systematically distorted. Distortion effects on estimating time to arrival and the scale of sketch‐maps reveal the nature of mental representation of time and space. Inspired by data from rodent entorhinal grid cells, we predicted that familiarity to an environment would distort representations of the space by expanding the size of it. We also hypothesized that travel‐time estimation would be distorted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 37 publications
5
11
0
Order By: Relevance
“…Beyond boundaries separating positions, our findings demonstrate that distance estimates can be influenced through the geometric arrangement of boundaries. The response profiles observed in the VR version of the task revealed a general tendency to overestimate distances between positions, consistent with previous studies reporting overestimations of navigated distances 58 and spatial scale in map drawings 59 . We used the distances estimated on a subjective scale in the desktop version of the task to reconstruct remembered positions.…”
Section: Discussionsupporting
confidence: 89%
“…Beyond boundaries separating positions, our findings demonstrate that distance estimates can be influenced through the geometric arrangement of boundaries. The response profiles observed in the VR version of the task revealed a general tendency to overestimate distances between positions, consistent with previous studies reporting overestimations of navigated distances 58 and spatial scale in map drawings 59 . We used the distances estimated on a subjective scale in the desktop version of the task to reconstruct remembered positions.…”
Section: Discussionsupporting
confidence: 89%
“…Beyond boundaries separating positions, our findings demonstrate that distance estimates can be influenced through the geometric arrangement of boundaries. The response profiles observed in the VR version of the task revealed a general tendency to overestimate distances between positions, consistent with previous studies reporting overestimations of navigated distances (Brunec et al, 2017) and spatial scale in map drawings (Jafarpour and Spiers, 2017). We used the distances estimated on a subjective scale in the desktop version of the task to reconstruct remembered positions.…”
Section: Discussionsupporting
confidence: 84%
“…However, the question remains as to why the participants did rely on the traveled distance to infer travel time and not vice versa? Though a causal link between neuronal activity and the observed time‐space interaction at a perceptual level remains speculative at this stage, the interrelation between interval timing and spatial processing is consistent with the findings regarding spatially and temporally tuned neurons in the hippocampus (Eichenbaum, ; Ekstrom & Ranganath, ; Howard & Eichenbaum, ; Jafarpour & Spiers, ; Ranganath & Hsieh, ). For example, Kraus et al () reported that hippocampal cells in rats exhibit increased firing at specific moments within a repeated 16 s interval of running on a treadmill.…”
Section: Discussionsupporting
confidence: 84%
“…In sum, stimuli comprised views of three different sized rooms, each presented for three different durations. Given that it was unclear whether spatial and temporal estimates might be affected by an environment's familiarity (Barry, Ginzberg, O'Keefe, & Burgess, ; Jafarpour & Spiers, ), the wall and ground textures were randomly varied to maintain the impression of constantly changing (i.e., novel) environments.…”
Section: Methodsmentioning
confidence: 99%